Nursing Undergraduate Students' Experiences and Perceptions of Blended Learning in Pediatric Nursing: A Mixed Methods Study - Yuanyuan Yang PhD; Hua Chen PhD; Hongyu Sun PhD (SAGE Publishing, 2024)
Introduction Blended learning is a teaching approach that integrates online self-learning and classroom teaching. It emphasizes students' self-directed learning, actively engaging, as well as communication and collaboration. Blended learning develops the qualities in nursing undergraduate students with problem-solving ability, clinical thinking, and communication skills as nurses have. Currently, learners' experience has become an important factor in determining the success of blended learning. Aim To learn about the experiences and perceptions of undergraduate nursing students regarding blending learning in pediatric nursing. Methods A mixed methods design beginning with a quantitative data collection and analysis phase to inform the subsequent qualitative phase was utilized. This study was conducted among undergraduate nursing students at one university in China. In the quantitative study phase, a convenience sample of 59 students completed the online survey while the qualitative study phase included nine students recruited by purposive sampling. The qualitative data were collected using individual semistructured in-depth interviews. Audio data were transcribed and subjected to thematic analysis. The findings from those two phases were integrated into the final analysis. Results The majority (89.8%) of students reported satisfaction with blended learning. Among various teaching methods, case-based learning (CBL) was the most preferred (98.3%). Regarding the qualitative data, students reported positive experiences with blended learning including well-organized course structure, resourceful course content, and high teacher quality. They stated that blended learning improved the learning outcomes such as improving problem-solving ability and developing clinical thinking. They also provided suggestions for achieving better learning outcomes, including providing stressful learning activities, optimizing online course design, and improving the quality of group learning. Conclusions The blended learning model of pediatric nursing based on the Community of Inquiry framework provides a positive learning experience for nursing undergraduate students. However, ongoing assessment and improvement of the blended learning process are also needed.